Memahami Ulang Makna Sosio-Ekologis Abad 21: Kespesiesan Manusia dan Personitas Alam dalam Anthropocene Melalui Actor-Network Theory - Fiktor Jekson Banoet (IAKN Ambon, 2022)
Tendency of the post-positivism sociology family to define the social meaning of humans as a way of living together between humans. The social meaning is drawn from the interactions between them and has not included the associative rules with the ecosphere (biotic and abiotic) as forming the social meaning. And conversely, certain parties, from among scientists, even environmental activists, do not include the definition of the environment as having a